Mircea Eliade în dialog „prin timp“ cu Edward Gordon Craig și/sau „Teatrul Viitorului“ ca o „Fata Morgana“ (II) - Mihuț, Anca-Daniela (Theatrical Research, 2023)
Mircea Eliade in dialogue “through time” with Edward Gordon Craig and/or “Theatre of the Future” as a “Fata Morgana” (II) "The Theatre of the Future” is a phrase present in the vast majority of theatrical theories that had the ambition to contribute to the renewed process of dramatic art at the beginning of the 20th century. Theoreticians and practitioners of the theatre wanted to restore the dignity of this art, redefining the condition and function of the actor, imagining the most effective ways of training him, promoting the emancipation of the stage director, seen as an indispensable factor of cohesion between spectacular elements; they redefined the framework and function of the performance that they imagined as an instrument of education, emancipation, even enlightenment and spiritual “salvation”, wanting also to liberate the theatrical creation from the submission to the dramatic author and the commercial servitude. If the first part of this article referred to the meeting, which, transcending time and space, put Mircea Eliade and Gordon Craig in a dialogue on the new dramaturgy and the experimental theatre, this second part brings into discussion their conception of the nature and aim of the theatre and about the ideal actor.